Time-cost trade-off in a multi index bi-criteria fixed charge transportation problem. (14th June 2019) - Singh, Sungeeta; Tuli, Renu; Sarode, Deepali
This paper is motivated by the necessity of finding efficient time-cost trade-off pairs for multi index bi-criteria fixed charge transportation problem wherein time criteria assumes greater significance than cost criteria and is therefore minimised first. So far no study on finding optimal time-cost pairs of the problem has been undertaken, a gap which the newly developed algorithm aims to fulfil. Results of a numerical illustration are obtained by the proposed algorithm by applying extended Vogel's approximation method and extended modified distribution method; it has been observed that the proposed algorithm is a far better alternative in problems in which time minimisation holds priority over cost minimisation.